Strategic database technology : management for the year 2000 - Simon, Alan R (Kaufmann, 1995)
Noted consultant Alan Simon\'s 11th book explores the potential of current and emerging database technologies. Technically serious, but not technically detailed, this book is designed to give information managers and others an overview of the trends and technologies for use in the years ahead so that they can be incorporated into the manager\'s plans today.
Keywords: Databáze